Automotive Collision Repair Video Series - Duffy, James E. (Delmar, 1998)
The series includes a basic safety tape and stresses safety throughout. Mr. Duffy has scoured the market for excellent footage from OEMs and aftermarket manufacturers and includes this to give the tapes a modern up to the minute look and feel. With many years experience producing instructional videos, James Duffy knkows how to create tapes that students will be able to unederstand and learn from, as well as keeping them interested in the presented material. Lively, educational, and modern, this new series will become a required part of instruction for automotive collision repair courses